WE WANT TO BE HEARD - Черная, Наталия Леонидовна (Mother and Baby in Kuzbass, 2017)
Polemical article is devoted to the analysis of contemporary issues in the provision of primary health care for children and training of graduates of pediatric faculties of medical universities to work as a district pediatrician. In the article the author presents his point of view on what should be the priority of conversion in the areas of medical education and health crisis of the state in which are now children's healthcare and graduate medical education
Keywords: medical education; primary health care to children